Retraction Note: Neonatal Hypoglycemia: Oral Dextrose Gel and Tahneek Practice - Çaksen, Hüseyin (Journal of Pediatric Epilepsy, 2023)
The above article published in Journal of Pediatric Epilepsy in Volume 12, Number 02 (DOI: 10.1055/s-0042-1760192), has been retracted as it is lacking scientific base.